Effects of inhaled bronchodilators on lung function and cycling performance in female athletes with and without exercise-induced bronchoconstriction. Issue 5 (September 2015) - Koch, Sarah; Karacabeyli, Derin; Galts, Ciaran; MacInnis, Martin J.; Sporer, Benjamin C.; Koehle, Michael S.
Abstract Objectives Inhaled β2-agonists may cause differential effects on lung function and athletic performance in female compared to male athletes. The objective of this study was to compare the effects of inhaled β2-agonists on lung function and cycling performance between female athletes with and without exercise-induced bronchoconstriction and with previously published data on men. Design Double-blind crossover randomized controlled trial. Methods Twenty-one female athletes (6 with exercise-induced bronchoconstriction and 15 without exercise-induced bronchoconstriction) performed a simulated 10-km time-trial on a cycle ergometer 60 min after the inhalation of either 400 μg of salbutamol or placebo. Forced expiratory volume in 1 s, was measured immediately before and 30 min after inhalation. Performance was measured by mean power output over the duration of the time trial. Results After salbutamol inhalation, Forced expiratory volume in 1 s improved significantly in athletes with exercise-induced bronchoconstriction (M (SD) = 6.1% (47.6)) and athletes without exercise-induced bronchoconstriction (4.0% (3.1); p ≤ 0.02). Mean power output was significantly decreased after salbutamol use (204 W (21)) compared to placebo (208 W (17); p = 0.047), regardless of airway hyperresponsiveness. Relative to placebo, salbutamol significantly increased mean oxygen consumption (46.9 mL kg−1 min−1 (5.9) vs. 44.8 mL kg−1 min−1 (4.0); p = 0.049) and significantly decreased cycling economy (72.8 W L−1 min−1 (6.8) vs. 76.4 W L−1 min−1 (4.3); p = 0.01). Conclusions The inhalation of salbutamol induced a significant increase in lung function in female athletes, but this increased lung function did not translate to improved exercise performance.